Shari'ah Standardization of Astrophotography for Rukyatul Hilal - Zain, Muhammad Fajri Kholili; Ubaidi, Muh. Izzat; Qiromi, Nur Mahmudi; Izzuddin, Ahmad; Hambali, Slamet (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2025)
The development of rukyatul hilal technology is growing very fast, one of them is the astrophotography technique used to take an image of the hilal so that it becomes a photo that can be seen many times. However, we need to know that the determination of the beginning of the qamariyah month is not entirely dependent on science, but what determines whether or not an image is accepted as the basis for changing the qamariyah month is in the realm of shari'a (fiqh). Problems arise related to the acceptance of astrophotography images as a basis for determining the change of qamariyah months in fiqh, and if it is allowed whether there are certain conditions in it. This research was written using the literature study method by tracing the rules of fiqh in classical and contemporary Islamic sources, which were then analyzed deductively in order to formulate a regulation. With this method, it was found that the use of astrophotography in rukyatul hilal is allowed. However, in order for the image to be accepted as the basis for proof, three (3) conditions must be fulfilled.